The Effect of Using Podcast Media on Maharah Istima' (Listening Skills) Students of Arabic Literature Study Program at University of Sumatera Utara - Lubis, Andi Pratama; Nasution, Fatimatuzzahra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Special Maharah'(listening skill) is one of the four linguistic skills, both listening (istima'), listening (kalam), reading (qira'ah) and writing (kitabah). Maharah Istima' (listening skill) is a language skill that USU Arabic Literature students learn for the first time before learning other language skills. Good and precise listening skills owned by USU Arabic Literature students will be the main capital for USU Arabic Literature students to master other language skills and make it easier for USU Arabic Literature students to master languages, especially Arabic. The Istima' course is one of the compulsory subjects offered by the Arabic Literature study program, University of North Sumatra. The learning process of Maharah Istima' (listening skills) is good, Appropriate learning methods and interesting learning media are needed to obtain maximum results. Considering that in the process there are still problems and obstacles in improving the listening skills of USU Arabic Literature students, Arabic Literature study program, University of North Sumatra. The purpose of the research to be carried out is todetermine the effect of using podcasts in improving listening skills (maharah istima') in Arabic Literature students of USU Arabic Literature University of North Sumatra. This study uses a quantitative method with a quasi-experimental model that uses data collection techniques through tests (both pre-test and post-test) then the data is analyzed by descriptive statistics and inferential statistics.